Carbamazepine as a single drug in the treatment of epilepsy. A prospective study of serum levels and seizure control. Issue 10 (October 1978) - Callaghan, N; O'Callaghan, M; Duggan, B; Feely, M
Abstract : Serum levels and seizure control were investigated in a prospective study when carbamazepine was given as a single drug to 32 patients with a variety of seizures. The patients included 13 previously untreated patients (group 1), and 19 who were unresponsive to other anticonvulsant drugs used in different combinations or as a single treatment (group 2). Thirteen patients (10 from group 1, and three from group 2) became seizure-free, and a greater than 50% reduction in seizure frequency occurred in 10 patients (nine from group 2, and one from group 1). Less than 50% reduction in seizure frequency occurred in five patients from group 2. As a wide range of serum levels was associated with complete freedom from seizures, or a greater than 50% reduction in seizure frequency, it was not possible to define a therapeutic range for carbamazepine. Side effects occurred at the start of treatment or after a dose increase. A wide range of serum levels was associated with side effects, and some patients could not tolerate levels greater than 42 mumol/l.